(untitled) (Journal of Teaching and Research in English Literature, 2014)
One significant observation of new criticism is the form of a text subsumes the content, i.e. the content is inseparably realised in the textual structure. Such a realization is achieved in Soyinka’s poem, “Telephone Conversation”. This article substantiates such synchronization by applying Beaugrande’s concept of ‘Textuality’. Such rigorous application of a theoretical structure as textuality, brings out the underlying racial discrimination of the text very effectively. De Beaugrande and Dressler (1981) have defined ‘Textuality’ as a set of ‘theoretical units’ which succeed in making connections wherever communication events occur. They have proposed seven standards of textuality – cohesion, coherence, intentionality, acceptability, informativity, situationality and intertextuality. These principles are constitutive principles of textual communication.